Perspicacity Customer Satisfaction of Online Banking: A Study in India - Chauhan, Saraswati; Singh, Netra Pal (Universitas Airlangga, 2024)
The usage of online banking by the banking sector has been expanding quickly as a practical and effective way to add value for customers. Faster and more dependable services for online consumers is one of the well-liked offerings from traditional banks. Online banking has the potential to draw in more clients to affiliated banks by taking use of the swift advancements in information technology. But the primary issue that providers of online banking are dealing with is that many bank customers are unwilling to use the services that are available for online banking. This occurred as a result of the fact that customers are still not satisfied with the services provided by online banking. A crucial component in assisting banks in maintaining their competitive advantages is customer satisfaction. Thus, the goal of this study is to identify and investigate the variables that affect customers' satisfaction with online banking. Customer satisfaction with online banking can be influenced by five factors: convenience, speed, security and privacy, web design and content, and service quality. 216 working adults who took part in the study were asked a series of questions (questionnaire), and their answers and comments on the aforementioned elements that affect customers' decisions to utilize online banking were very insightful. The study's findings revealed that the top three factors influencing consumers' satisfaction with online banking are ease of use, speed, and web design and content.